Weyl's theorem and tensor products: a counterexample. - KITSON, DEREK (Elsevier, 2011)
Approximately fifty percent of Weyl's theorem fails to transfer from Hilbert space operators to their tensor product. As a biproduct we find that the product of circles in the complex plane is a limacon.
PUBLISHED
Keywords: Mathematics; Weyl's theorem; Browder's theorem